JURIDICAL ANALYSIS OF THE BANKRUPTCY EXECUTION DECISION UNDER INDONESIAN COMMERCIAL COURT - Savitri, Ravina; Santoso, Budi (Tadulako Law Review, 2021)
Bankruptcy is a civil law institution as the realization of the two main principles contained in Article 1131 and Article 1132 of the Civil Code. The effect of bankruptcy is only on the assets of the debtor, where the debtor is not under supervision. The debtor does not lose his ability to carry out legal actions unless the legal action involves the management and transfer of his existing property. Meanwhile, execution is the implementation of a Court Decision which has permanent legal (in kracht van gewijsde), after the debtor is declared bankrupt, the bankruptcy process will be carried out. The main purpose of conducting bankruptcy is to share the debtor's assets with its creditors and this must be done by the curator after there is a bankruptcy decision. This study uses a normative juridical approach, which means that this research is conducted by examining existing literature such as laws and regulations, related books, as well as dictionaries or encyclopedias. This approach is carried out with the intention that researchers get information from various aspects of the issue being tried to find answers. The Bankruptcy Law explains several factors regarding the need for bankruptcy regulations and postponement of debt payment obligations. The bankruptcy verdict greatly affects the execution. As a result of the declaration of bankruptcy, the entire determination of the debtor's assets obtained before being declared bankrupt must be terminated and since then no decision has been made. A bankrupt debtor may be subject to gijzeling action. This gijzeling institution is primarily shown if the bankrupt debtor is not cooperative in resolving bankruptcy as regulated in Articles 93-96 of the Bankruptcy Law. Legal remedies in bankruptcy proceedings did the abolition of appeal legal remedies is intended to cut the judicial pathway in the bankruptcy process to make it more effective